The interaction of miR-34b/c polymorphisms and negative life events increases susceptibility to major depressive disorder in Han Chinese population. (9th June 2017) - Xu, Cheng; Yang, Chunxia; Zhang, Aixia; Xu, Yong; Li, Xinrong; Liu, Zhifen; Liu, Sha; Sun, Ning; Zhang, Kerang
Highlights: The significance of miR-34b/c gene polymorphisms in MDD was evaluated. The rs4938723 and rs2187473 polymorphisms were associated with stratified MDD by discarding subjects with severe negative life events in the dominant models. C-G haplotype (rs4938723/rs28757623) showed the strongest association with stratified MDD. Significant gene–environment interaction between the C-G haplotype (rs4938723/rs28757623) and negative life events associated with MDD risk. Abstract: Background: Previous studies have shown that microRNAs(miRNAs) are involved in the pathogenesis of MDD; in particular, miR-34b/c has been implicated in MDD risk and found to exert antidepressant effects. However, the effects of miR-34b/c polymorphisms on MDD risk have not been investigated. Methods: In this study, we evaluated the effect of miR-34b/c gene polymorphisms and their interaction with negative life events in relation to MDD, using data from 381 Han Chinese patients with MDD and 291 healthy volunteers. Allelic, genotypic, haplotypic, and gene-environment associations were analyzed using UNPHASED and SPSS software. Results: After discarding data with extremely severe negative life events in our study population, we found an association between rs4938723, rs2187473 polymorphisms and MDD in the dominant models (TC/CC vs. TT, OR = 1.45, P = 0.027; TC/CC vs. TT, OR = 3.32, P = 0.030). In haplotype analysis, the C-G haplotype (rs4938723/rs28757623) showed the strongest association with MDD (OR = 1.95, P = 0.026). Additionally, we found significant gene-environment combination rs4938723 C allele, rs28757623 G allele and high level of negative life events (C-G-HN) was significantly associated with MDD (OR, 3.85; 95% CI, 1.62–9.13). In addition, the combination of (C-C-HN) is of significance (OR, 2.99; 95% CI, 1.36–6.60), indicating that the rs28757623 C allele may contribute to the risk of MDD as well. Limitations: The sample size was small and the role of miR-34b/c polymorphisms for MDD should be assessed using independent samples from other ethnic populations. Conclusions: Our results suggest that miR-34b/c is a susceptibility factor for MDD stratified by negative life events and that rs4938723 is a significant association locus for gene-environment interaction in relation to MDD risk.